A Semiotic Analysis of Traditional Carvings in Traditional Houses of Orahili Sibohou Village, Gomo, South Nias - Afore Harefa; Clara Harefa; Maria Halawa; Anjelina Ndruru (Journal of Innovative and Creativity, 2026)
This study aims to uncover the semiotic meanings of traditional carvings in Nias traditional houses (Omo Hada) in Orahili Sibohou Village, Gomo, and to compare the visual and social characteristics between noble houses (Balugu/Si’ulu) and commoner houses (Banua Sato). The research employs a descriptive qualitative method with a semiotic approach. Primary data were gathered through direct observation of a ±500-year-old traditional house and in-depth interviews with the customary leader and heir of the Balugu house, Mr. Tandröziduhu Telaumbanua (A. Uco). The study is further supported by a literature review of "Bahasa dan Sastra Nias" (Zendratö, 2003), comparative statements from residents of Tumöri Village, and curatorial perspectives from the Museum Pusaka Nias tour guide, Filemon Soalisökhi Hulu. The results indicate that carvings on Balugu houses serve as representations of power, social status, and historical achievements through traditional feasts (Owasa). Semiotically, the use of high-quality Siholi wood and exclusive motifs signifies a rigid class hierarchy. In contrast, commoner houses possess limited carvings due to financial constraints and customary regulations. Although motifs such as Ni’olasara can theoretically be placed in various types of houses, the practice in Orahili Sibohou demonstrates that the complexity of carvings remains the primary marker of social status. The study concludes that carvings and megalithic objects in Gomo are vital artifacts documenting the Fondrako (customary law system) and Nias cultural identity, which remains significant despite ongoing social shifts.